SIMULATION OF COFFEE FRUIT DRYING USING COMPUTATIONAL FLUID DYNAMICS - Amaral, Rudney; Andrade, Ednilton Tavares; Gomes, Francisco Carlos; Borém, Flávio Meira; Lemos, Isabella; Dias, Camila Almeida (Coffee Science - ISSN 1984-3909, 2018)
Drying is a fundamental step in post-harvest handling of coffee because moisture content at the end of drying affects several important aspects, such as sensory quality, storability, and color. Within this context, the aim of this study is to determine water distribution within the natural coffee fruit during and at the end of the drying process. For that purpose, simulations were made through finite elements using computational fluid dynamics. Experimental data on moisture content of coffee fruitin the “cherry” stage were collected during drying, which was carried out at a temperature of 40°C and relative humidity of 25% to 0.18 decimal(dry basis – d.b.)to compare the results of the experiment with the results of the simulations. Ten mathematical models of the drying process were developed for the collected data. The two-term exponential model best fit the data. The results of the simulations in computational fluid dynamics were compared to the results from experimental drying, and a satisfactory fit was obtained. The effective diffusivity coefficient (Deff) was developed for the model, obtaining the value of 2.87 x 10‑11 m2 s-1. At the end of drying, the model exhibited 57.1% of the projection area of the coffee fruit with moisture content below 0.18 decimal (d.b.). Thus, the model can be used for other applications.